Produktivitas dan Ketahanan Galur Harapan Padi terhadap Penyakit Tungro di Sumatera Selatan - Tumarlan Thamrin; Imelda Suryani Marpaung; Syahri Syahri (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2012)
Thamrin et al. 2012. Productivity and Resistancy of the Tungro-resistant Rice Variety in South Sumatra. JLSO 1(2):130-137. The establishment of new varieties is required to have the advantage of being more diverse and specific according to agroecosystem, problems in the field, the specific location and consumersâ€™ preference. Prior to its establishment, a tungro-resistant rice variety needs to be tested locally. This research was carried out on the rain-fed rice field at the village of Lubuk Seberuk Sub-district Lempuing, Ogan Ilir Komering Regency (OKI) Â in 2009.Â This research employed randomized block design (RGD) with 10 treatments consisted of eight strains and two improved varieties as a comparison. Each treatment was repeated 3 times. The results indicated that strain B-10018G-TB-42-1 has the least tungro attacks and the highest number of tillers and production compared to the other strains and varieties.